ASSOCIATION BETWEEN SUGAR-SWEETENED BEVERAGE CONSUMPTION AND BODY MASS INDEX AMONG UNIVERSITY STUDENTS IN KUALA NERUS, TERENGGANU, MALAYSIA - Aida Aliah Abu Bakar; Hussin, Napisah; Abbe Maleyki Mhd. Jalil; Marhazlina Mohamad (Malaysian Journal of Public Health Medicine, 2020)
Overweight and obesity are major health concerns in Malaysia, which are linked to other health consequences such as type 2 diabetes mellitus, cardiovascular diseases and several others. Among dietary factors, sugar-sweetened beverages (SSBs) are reported to be one of the leading factors of weight gain and a higher body mass index (BMI). Sugar-sweetened beverages are beverages with added sugar that only add calories to an individual’s normal diet and they represent the largest contributor to the added sugars intake. This study was aimed to determine the prevalence of SSB consumption among university students in Kuala Nerus, Terengganu, as well as to investigate the association between the students’ SSB consumption and their BMI. A cross-sectional study was conducted among 350 Universiti Sultan Zainal Abidin (UniSZA) Gong Badak Campus and Universiti Malaysia Terengganu (UMT) students by using the convenience sampling. Each participant was given a questionnaire consisting of socio-demographic details, anthropometric assessment and beverage intake. The results revealed that half of the students consumed 2 cups (500 mL) of SSBs on average days (49.4%), whereas 21.7% of them consumed at least 3 cups daily. It was found that sweetened tea was the students’ most preferred SSB and there was also an association between the SSB consumption and the BMI. In conclusion, university students in Kuala Nerus drink 2 cups of SSBs daily and sweetened tea is their preferred SSB. Since the students’ SSB consumption influences their BMI, these students must be aware on the contents of SSB and the related health consequences in order to reduce the consumption of these beverages and hence, reduce their BMI to a healthy level.